The effect of ethanol extract of Wuru Ketek Leaves (Myrica javanica Reinw. ex Bl.) on the relative weight of organs in Male White Mice (Mus musculus L.) with alloxan-induced diabetes. - Anna Uswatun Hasanah Rochjana; Varda Arianti; Devi Maulina; Fani Aprilia (Indonesian Journal of Health Science, 2026)
Wuru Ketek (Myrica javanica Reinw. ex Bl.) plant is known to contain flavonoids and tannins that have the potential as antidiabetics. This study aims to evaluate the effect of ethanol extract of wuru ketek leaves (Myrica javanica Reinw. ex Bl.) on the relative weight of the liver, kidneys, and heart of alloxan-induced diabetic male mice. A total of 30 mice were divided into six groups: normal group, negative control, positive control (glibenclamide), and three treatment groups with doses of 100, 200, and 300 mg/kgBW for 12 days orally. The organs were weighed and analyzed statistically. The results showed no significant difference in relative organ weight (p>0.05) between the treatment group and the normal group. These findings indicate that the ethanol extract of wuru ketek leaves (Myrica javanica Reinw. Ex Bl.) does not show toxic effects on target organs in the short term. Further studies are needed to assess long-term safety and other biochemical parameters.